Attaining Quality Matters Certification for a Registered Nurse-Bachelor of Science in Nursing Program. - Bryan, Carol S.; Oberlander, James F.; Reuille, Kristi M.; Lewandowski, Kelly Ann; Topp, Robert; Grothaus, Liz; Suh, Sylvia M. (CIN: Computers, Informatics, Nursing, 2021)
I ncreased demand for nurses and improved technology have increased the development and popularity of online education programs over the past two decades; however, the online format has revealed numerous pedagogical and implementation challenges. One primary challenge is the lack of structural design standards across all courses in the program. The lack of standardization is linked to decreased student outcomes, satisfaction, and retention. The Quality Matters course design rubric and program certification provide a methodical process to standardize the format of all courses in an online education program. The Quality Matters course rubric is designed to increase student and faculty engagementand reduce variability in course design. Atthe current university, the application of Quality Matters processes and standards was first trialed with a few individual courses. Following the trial, faculty and administration decided to begin the process of seeking Quality Matters certification for the entire registered nurse-bachelor of science in nursing program. This article describes the process of attaining Quality Matters program certification for an online registered nurse-bachelor of science in nursing program. The nursing process and the Human Performance Technology evaluation model were used as appraisal frameworks guiding this program's QM certification process.